Performance Evaluation of Asymmetric Encryption Algorithm (MQQ-ENC) in Wireless Multimedia Sensor Networks - معلا, بشرى; اسكندر, خديجة (Latakia University Journal -Engineering Sciences Series, 2021)
Wireless Multimedia Sensor Network (WMSN) consists of a large number of small size, low power, limited sources sensor nodes, deployed in tested field, These nodes have the ability of sensing, processing, storing and sending multimedia data from the tested field in real time. The security in WMSNs is one of most important issues that should be studied due to the special nature of this network, and of the importance of inquest basic security requirements when sending information in the network. Using cryptography technics are very effective ways to realize basic security requirements in this network. The recently proposed MQQ algorithm is one of public key cryptography (PKC) algorithms, which provides a good performance compared to other PKC algorithms. In this research, we present an analyzing study of MQQ implementation in WMSNs. To achieve our goal, we used real images taken by multimedia wireless sensor nodes. We studied the most important parameters such as the size of generated keys and encrypted images, the execution time and the space occupied in the flash memory of multimedia wireless sensor nodes and complexity degree of this algorithm. Results showed that MQQ has good performance, as well as the execution time of operations is better than RSA algorithm. Results also showed the importance of taking into account a large size of public key of MQQ algorithm when implementation it in WMSNs.